2017
DOI: 10.1021/acs.jpclett.7b00978
|View full text |Cite
|
Sign up to set email alerts
|

Au@Void@Ag Yolk–Shell Nanoclusters Visited by Molecular Dynamics Simulation: The Effects of Structural Factors on Thermodynamic Stability

Abstract: Au@void@Ag yolk-shell nanoclusters were studied by molecular dynamics simulation in order to study the effects of core and shell sizes on their thermodynamic stability and structural transformation. The results demonstrated that all of simulated nanoclusters with different core and shell sizes are unstable at temperatures lower than 350 K in such a way that Ag atoms are collapsed into the void space and fill it, which leads to creation of a more stable core-shell morphology, and at the melting point, only core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 96 publications
2
13
0
Order By: Relevance
“…As obvious from Figure , especially in Figure b, all of the Au@void@AgAu nanoclusters with different morphologies are unstable at room temperature in such a way that Ag and Au atoms of the shell region are collapsed into the void space to increase their coordination number and create more stable Au@AgAu core–shell (CS) structures. These results are in good agreement with our previous investigation on Au@void@Ag YSNPs, for which it was indicated that they are unstable at temperatures lower than 350 K and the void space is completely filled near this temperature . Another interesting result of Figure is considerable retaining of the morphologies of the core and shell regions after collapse of Ag and Au atoms into the void space at 300 K for final core–shell structures in comparison with the initial YS ones.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…As obvious from Figure , especially in Figure b, all of the Au@void@AgAu nanoclusters with different morphologies are unstable at room temperature in such a way that Ag and Au atoms of the shell region are collapsed into the void space to increase their coordination number and create more stable Au@AgAu core–shell (CS) structures. These results are in good agreement with our previous investigation on Au@void@Ag YSNPs, for which it was indicated that they are unstable at temperatures lower than 350 K and the void space is completely filled near this temperature . Another interesting result of Figure is considerable retaining of the morphologies of the core and shell regions after collapse of Ag and Au atoms into the void space at 300 K for final core–shell structures in comparison with the initial YS ones.…”
supporting
confidence: 92%
“…Our results showed that YSNPs with the largest core and shell (i.e., minimum void space) demonstrated the highest thermodynamic stability and melting point. In fact, we showed the core and shell size effect on the stability and melting behavior of YSNPs, cooperatively . Since then, recent studies have exhibited that both the structural and thermodynamic stabilities of bimetallic nanoclusters depend on their composition, size, and morphology, and hence we believe that the mentioned factors may have a great effects on the stability of YSNPs, which are important for their potential application in catalysis and other fields of nanotechnology.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…The temperature of the systems was controlled using Nosé–Hoover thermostat with a relaxation time of 0.1 ps. Previous works have also used successfully the same relaxation time for this thermostat . To investigate whether our systems have been achieved the equilibrium and stability, we have drawn the graphs of configurational energy, total energy, and temperature versus the simulation time for the different systems considered in this work and presented in Supporting Information Figures S5–S7.…”
Section: Simulation Detailsmentioning
confidence: 99%